Literatura jako mit i hipertekst w powieści „Bieskoniecznyj tupik” Dmitrija Gałkowskiego (próba rekonstrukcji koncepcji historiozoficznych) - Szubin, Roman (Studia Rossica Posnaniensia, 2016)
This article is devoted to reconstruction of the historiosophical concept in Dmitry Galkovsky's novel The Infinite Deadlock (Бесконечный тупик). The author pays particular attention to the criteria of historiosophy: mythologism, ambivalence of consciousness, hesychast tradition, eidetic language, a universal man (absolute personality). He highlights the demythological factor in Galkovsky's creative work, its cultural and national nihilism. The author analyzes the image of the main character's identity, who is capable of identifying himself, who is humiliated or ingenious. In passing, the author considers the idea of common history in which the eras which dialectically deny each other's coexistence.